2019 IEEE International Symposium on Information Theory (ISIT) 2019
DOI: 10.1109/isit.2019.8849596
|View full text |Cite
|
Sign up to set email alerts
|

On Coding Over Sliced Information

Abstract: The interest in channel models in which the data is sent as an unordered set of binary strings has increased lately, due to emerging applications in DNA storage, among others. In this paper we analyze the minimal redundancy of binary codes for this channel under substitution errors, and provide several constructions, some of which are shown to be asymptotically optimal. The surprising result in this paper is that while the information vector is sliced into a set of unordered strings, the amount of redundant bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
19
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 21 publications
1
19
0
Order By: Relevance
“…In [13], unordered multisets with errors that affect the whole sequence have been discussed. Furthermore, the model proposed in this work has already been adopted in [14], [15]. Namely, codes and bounds for an arbitrary number of substitutions in sets of DNA strands have been derived in [14] and it has been shown that it is possible to construct codes, which have logarithmic redundancy on both, the number of sequences and the length of the sequences.…”
Section: Introductionmentioning
confidence: 99%
“…In [13], unordered multisets with errors that affect the whole sequence have been discussed. Furthermore, the model proposed in this work has already been adopted in [14], [15]. Namely, codes and bounds for an arbitrary number of substitutions in sets of DNA strands have been derived in [14] and it has been shown that it is possible to construct codes, which have logarithmic redundancy on both, the number of sequences and the length of the sequences.…”
Section: Introductionmentioning
confidence: 99%
“…Some recent works have focused on coding for other channel models inspired by DNA-based storage. The model studied in [27,28,29,30] views codewords as sets comprised of several sequences over some alphabet, and the (adversarial) errors consist of erasure and insertion of sequences in the set, as well as deletions, insertions, or substitutions within some of the sequences. Each sequence in the set corresponds to a different DNA strand whose contents are reconstructed via high throughput sequencing-based procedures that introduce errors.…”
Section: Introductionmentioning
confidence: 99%
“…Codes dealing with insertion/deletion errors were also studied in [11]. Codes that can correct a total of K substitution errors were studied in [12] using the sphere packing arguments, which is essentially the same as the error ball arguments.…”
Section: Introductionmentioning
confidence: 99%